2008
DOI: 10.1038/onc.2008.366
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of FLIP and XIAP induces Bax-independent apoptosis in type II colorectal cancer cells

Abstract: Death receptors can directly (type I cells) or indirectly induce apoptosis by activating mitochondrial-regulated apoptosis (type II cells). The level of caspase 8 activation is thought to determine whether a cell is type I or II, with type II cells less efficient at activating this caspase following death receptor activation. FLICE-inhibitory protein (FLIP) blocks death receptor-mediated apoptosis by inhibiting caspase 8 activation; therefore, we assessed whether silencing FLIP could convert type II cells into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 49 publications
6
42
0
1
Order By: Relevance
“…35 and 36). Many previous studies have shown that knockdown or downregulation of c-FLIP results in ligand-independent, but caspase-8-dependent, spontaneous apoptosis (37)(38)(39). Thus, our observation that ␥-secretase inhibitor, which inhibited the turnover of both c-FLIP L and c-FLIP S , also partially blocked PS1-induced apoptosis strongly suggests that PS1-induced apoptosis is at least partially mediated by ␥-secretase-catalyzed turnover of c-FLIP.…”
Section: Discussionsupporting
confidence: 57%
“…35 and 36). Many previous studies have shown that knockdown or downregulation of c-FLIP results in ligand-independent, but caspase-8-dependent, spontaneous apoptosis (37)(38)(39). Thus, our observation that ␥-secretase inhibitor, which inhibited the turnover of both c-FLIP L and c-FLIP S , also partially blocked PS1-induced apoptosis strongly suggests that PS1-induced apoptosis is at least partially mediated by ␥-secretase-catalyzed turnover of c-FLIP.…”
Section: Discussionsupporting
confidence: 57%
“…For the other part, increasing caspase-8 activity, for example by downregulating c-FLIP, does not automatically convert type 2 into type 1 cells. 98 This can probably be attributed to the action of XIAP, 99 which can directly bind and inhibit the effector caspases (-3 and -7; and also active caspase-9, although with much weaker affinity). 79 High levels of XIAP would be predicted to attenuate Fas-induced apoptosis signalling at a much more downstream stage, targeting and blocking processed effector caspases.…”
Section: Xiap and Type 1 Versus Type 2 Fas-induced Apoptosis Signallingmentioning
confidence: 99%
“…Experimental manipulation of FLIP (Wilson et al, 2007) and XIAP (Toscano et al, 2008;Connolly et al, 2009;Wilson et al, 2009) has confirmed their critical role in mediating resistance against TRAIL-R-dependent apoptosis. High levels of the anti-apoptotic proteins Bcl-xL (Schulze-Bergkamen et al, 2008), BAG-1 (Clemo et al, 2008), AKT, and Bax (Niyazi et al, 2009) also mediate TRAIL resistance in colorectal cell lines.…”
Section: Discussionmentioning
confidence: 99%